Analysis of the Crime of Money Laundering with Counterfeiting and Money Laundering Together and Continuing (Case Study of Supreme Court Decision No. 4857 K/Pid.Sus/2024) - Muda Sipayung, Iskandar (International Asia Of Law and Money Laundering (IAML), 2025)
This paper departs from the problems of any criminal acts related to money laundering as supplementary crimes and is there a legal basis to apply pengga / ihan burden absolute proof (shifting burden of proof~ in the process of money laundering. Results the study concluded, that the falsification of letters that become predicate crime. Legal basis for applying the absolute transfer of the burden of proof (shifting burden of proof in the process of money laundering applied Article 263 Paragraph (1) Criminal Code juncto Article 55 Paragraph (1) to 1 Criminal Code juncto Article 64 Paragraph (1) Criminal Code, Article 3 juncto Article 10 law. Law No. 8 of 2010 on prevention and Eradication Money laundering in conjunction with Article 64 Paragraph (1) of the Criminal Code, Law- Law No. 8 of 1981 on Criminal Procedure Law, Law- Law No. 48 of 2009 on Judicial Power, and Law No. 14 of 1985 on the Supreme Court as amended by Law No. 5 of 2004 and the Second Amendment To Law No. 3 of 2009, the point is that the original crime or predicate crime is not required to be proven first.